(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Self-help Groups plays a very imperative role in rural women upliftment in India. Institutional credit through micro finance has now emerged as a financial strategy to reach the urban and rural poor and is emerging as a movement at the global level. Over the past two decades, institutional credit through micro finance has acquired greater dimension and recognition as an instrument for meeting the credit needs of the poor for their income generating activities. The institutional credit support extended to the self-help groups together with other extension support such as skill upgradation, enhancing entrepreneurial abilities along with providing necessary infrastructures and marketing support helps the self-help groups to cross the barriers that keep them below the poverty line. This research study attempt to examine the impact of institutional credit on the development of rural women through self-help groups